Implementation of the défense public policy defend the state in Indonesian Universities - Lukman Yudho Prakoso; Gazali Salim; Julian Ransangan; Subhilhar; Agus Indarjo; Yusriadi Yusriad (Allied Business Academies, 2021)
Indonesia in May 2018 was again shocked by the act of terrorism in the form of an explosion that occurred in urban areas on three Surabaya churches carried out by one family, the next action was an explosion in the North Surabaya Police Resort City with a suicide bombing involving one family as well. This fact is an indicator that the nation must re-evaluate the country's defence, which is carried out by the people. The perpetrators have been living with the community all this time but have escaped our mutual attention. Terrorism and radicalism cases also continue to thrive among universities, both state and private, especially those in urban areas. Therefore, it is necessary to re-examine how the implementation of state defence which has been carried out in higher education. In this study the method used is descriptive phenomenological quality and the theory used is the theory of public policy implementation George Edward III. The results of the study show that communication between stake holders is still running independently and has not been integrated and coordinated optimally, the resources used are still carried out individually which results in ineffective and inefficient, disposition (authority) regarding state defence still has its own perceptions between agencies, the bureaucratic structure also has not shown the achievement of effective and efficient goals.